Pembelajaran Terpadu pada Siswa Miskin Pendidikan Usia Dini di Pekanbaru - Musnar Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2016)
Today the level of formal education in Early Childhood Education (ECD) a good many contributed to the preparation of children to basic education. However, the availability of early childhood education for poor children in urban areas is very limited presence, in addition to the difficulty of managing the funds needed for facilitating learning is also a factor in the lack menentuannya learners follow a schedule of learning. Implementation costs perdatang education and the design of integrated learning and involve their parents in the management of self-funding, is an alternative that can be developed. This study uses a methodology deep field surveys in a sample of poor children in the studio playing excelend Pekanbaru and involved 15 respondents parents. Meanwhile, to determine the application of an integrated learning approach used classroom action research which involves a number of teachers and observers. From the research results can be stated that: (1) Background of parents of children studying in general have realistic conditions of structural poverty, that the parents of the workers were uneducated and untrained and entrepreneurs without capital and without the facilities to the economy is very weak (2) the education level of parents is very low. Average not finish elementary school, (3) Revenue parents daily about Rp 20,000, - to 30,000, -rupiah, the financial burden shouldered by family members on average three people, (4) average child getting less nutrition balanced, because several things including; (A) the availability of food that is less due to the purchasing power of low food needs of parents, (b) knowledge of parents on nutritional patterns are also low due to inadequate education, (c) a culture of poor results in irregular eating patterns and food potluck menu.